Case report: EBV-related eye orbits and sinuses lymphohistiocytic infiltration responsive to rituximab in a patient with X lymphoproliferative syndrome type 1 - Giardino, Giuliana; Lanni, Vittoria; Mascolo, Massimo; Russo, Daniela; Cirillo, Emilia; Romano, Roberta; Cillo, Francesca; Grilli, Laura; Prencipe, Maria Rosaria; Iuliano, Adriana; Uccello, Giovanni; De Fusco, Carmela; et al. (Frontiers in Immunology, 2024)
X lymphoproliferative syndrome type 1 (XLP1) is a rare inborn error of immunity due to mutations of SH2D1A, encoding for SAP. Clinical phenotype includes severe mononucleosis, hemophagocytic lymphohistiocytosis (HLH) and B-cell lymphomas.We report the case of a child affected with XLP1 who presented with an incomplete HLH, triggered by EBV and treated with rituximab, involving orbits and paranasal sinuses.The lesion was indistinguishable from lymphoma complicating diagnosis and treatment, also considering high incidence of lymphoma in XLP1 patients: histology helped define its nature, driving therapeutic choices.We described an unusual presentation of incomplete HLH in a patient affected with XLP1: an EBV-driven infiltration of the orbits and paranasal sinuses. This had us confront with a challenging differential diagnosis with lymphoma-associated hemophagocytic syndrome which can be frequently observed in XLP1 patients. Considering the extremely poor prognosis of this clinical suspect, we sought after a prompt diagnosis and managed to reach it and to establish the right treatment on the basis of the pathological finding straight away.